Organizational participation, character development, and digital competence: Building teacherpreneurship in vocational teacher education under the Merdeka Belajar framework - Siti Mariah; Mark Gabriel Wagan Aguilar; Ika Wahyu Kusuma Wati; Amelia Jarapa (Jurnal Pendidikan Vokasi, 2025)
Teacherpreneurship has emerged as a strategic response to the growing demand for teachers who are not only pedagogically competent but also creative, opportunity-driven, and digitally literate. However, limited empirical evidence explains how organizational participation and character formation interact to shape entrepreneurial readiness among prospective vocational teachers, particularly within the Merdeka Belajar framework. This study employs an explanatory sequential mixed-methods design to examine the relationships between organizational participation, character development, and teacherpreneurship. Quantitative data were collected from 120 students using validated instruments, followed by qualitative interviews, focus group discussions, and observations involving 24 purposively selected participants. Statistical analyses, including multiple regression and structural equation modeling, indicate that organizational participation significantly predicts teacherpreneurial readiness, with character development acting as a partial mediator. Students demonstrated strong creativity, leadership, and digital competence, yet faced persistent challenges related to risk-taking, time management, institutional bureaucracy, and limited commercialization literacy. The qualitative findings further reveal identity shifts as students increasingly positioned themselves as innovators capable of developing educational products and digital learning services. SWOT analysis highlights that technological advancement and flexible curriculum opportunities outweigh threats such as competition and automation. The study concludes that teacherpreneurship requires a synergistic integration of experiential organizational learning, character education, and digital entrepreneurship training. Implications are directed toward vocational teacher education institutions to embed credit-bearing organizational engagement, structured mentorship, and micro-grant schemes aligned with Merdeka Belajar policies. These findings contribute to expanding theoretical perspectives on teacherpreneurship while offering practical strategies for strengthening vocational teacher preparation in rapidly evolving educational ecosystems.